Cognitive processes of apathy in Huntington’s disease show high sensitivity to disease progression - Emily Hare; Anne-Catherine Bachoud-Lévi; Ralf Reilmann; David Craufurd; Monica Busse; Anne Rosser; Duncan McLauchlan (Clinical Parkinsonism & Related Disorders, 2022)
Background: Disease-modifying treatments for Huntington’s disease (HD) are entering clinical trials: there is a pressing need for objective outcome measures of disease progression. Our previous work showed an association between 2 novel, objective cognitive tasks and apathy - a core feature of disease progression in HD. Objective: Evaluate the longitudinal validity and sensitivity of the novel Persistence and Maze tasks to assess their utility as clinical outcome measures in HD. Methods: 83 participants positive for the HD gene and 54 controls performed a battery of established and novel tools, at baseline and 12 month follow up. Results: The Maze task was found to be the most sensitive measure of change at 12 months, including the current gold-standard measure (the composite disease progression score). Conclusion: The Maze task has potential as a novel outcome measure of disease progression in HD and may have utility in other major neurodegenerative diseases.